Determinants of constitutional change: Why do countries change their form of government? - Bernd Hayo; Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
A country's form of government has important economic and political consequences, but the determinants that lead societies to choose either parliamentary or presidential systems are largely unexplored. This paper studies this choice by analyzing the factors that make countries switch from parliamentary to presidential systems (or vice versa). The analysis proceeds in two steps. First, we identify the survival probability of the existing form of government (drawing on a proportional hazard model). In our model, which is based on 169 countries, we find that geographical factors and former colonial status are important determinants of survival probability. Also, presidential systems are, ceteris paribus, more likely to survive than parliamentary ones. Second, given that a change has taken place, we identify the underlying reasons based on panel data logit models. Wefind that domestic political factors are more important than economic ones. The most important factors relate to intermediate internal armed conflict, sectarian political participation, degree of democratization, and party competition, as well as the extent to which knowledge resources are distributed among the members of society.
Keywords: H11; K10; P48; 330; constitutional change; institutional dynamics; form of government; endogenous constitutions; separation of powers; Verfassungsreform; Politische Reform; Staatsoberhaupt; Parlamentarismus; Gewaltenteilung; Institutioneller Wandel; Public Choice; Welt